Neuropshycological recovery dynamics in patients with ischemic stroke and alcoholic encephalopathy - Ye. A. Kladova; B. M. Doronin (Бюллетень сибирской медицины)
Examination of recovery dynamics of cognitive impairments in patients with ischemic stroke and with or without alcoholic encephalopathy was conducted. It was shown that in patients with ischemic stroke and alcoholic encephalopathy dementia prevails, and positive dynamics is extremely rare.